2008
DOI: 10.1073/pnas.0807866105
|View full text |Cite
|
Sign up to set email alerts
|

L1 recombination-associated deletions generate human genomic variation

Abstract: Mobile elements have created structural variation in the human genome through their de novo insertions and post-insertional genomic rearrangements. L1 elements are a type of long interspersed element (LINE) that is dispersed at high copy numbers within most mammalian genomes. To determine the magnitude of L1 recombination-associated deletions (L1RADs), we computationally extracted L1RAD candidates by comparing the human and chimpanzee genomes and verified each of the L1RAD events by using wet-bench analyses. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
124
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 38 publications
3
124
1
Order By: Relevance
“…They can generate structural variation through insertion-mediated deletion, in which the insertion of an L1 element can result in the deletion of the adjacent genomic sequence (Symer et al 2002;Gilbert et al 2002Gilbert et al , 2005 and via nonallelic homologous recombination between L1s that can create insertions, deletions, and inversions (Han et al 2008;Cordaux and Batzer 2009). Active L1s have been shown to be a major source of variation within the human population (Beck et al 2010;Huang et al 2010;Iskow et al 2010) and can modulate gene expression, for example, by alternative splicing (Belancio et al 2006), disrupting transcription (Han et al 2004), and generating alternative promoters (Speek 2001).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…They can generate structural variation through insertion-mediated deletion, in which the insertion of an L1 element can result in the deletion of the adjacent genomic sequence (Symer et al 2002;Gilbert et al 2002Gilbert et al , 2005 and via nonallelic homologous recombination between L1s that can create insertions, deletions, and inversions (Han et al 2008;Cordaux and Batzer 2009). Active L1s have been shown to be a major source of variation within the human population (Beck et al 2010;Huang et al 2010;Iskow et al 2010) and can modulate gene expression, for example, by alternative splicing (Belancio et al 2006), disrupting transcription (Han et al 2004), and generating alternative promoters (Speek 2001).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Transposable elements (TEs), once labeled as ''junk'' DNA, contribute to unprecedented levels of interspecific divergence (Lander et al 2001; The Chimpanzee Sequencing and Analysis Consortium 2005; Han et al 2007; Rhesus Macaque Genome Sequencing and Analysis Consortium 2007), intraspecific genome diversity (Batzer and Deininger 2002;Bennett et al 2004;Seleme et al 2006;Han et al 2008), and human diseases such as hemophilias A and B, as well as common cancers (Batzer and Deininger 2002;Chen et al 2005). Recently, the intra-and interchromosomal distributions of short and long interspersed nuclear elements (SINEs and LINEs, respectively), the most abundant classes of TEs in primate genomes (Rhesus Macaque Genome Sequencing and Analysis Consortium 2007), have received critical attention.…”
mentioning
confidence: 99%
“…The similarity between L1-A and L1-B was high (99.0%), and the interval was shorter than that of the human lineage-specific L1 recombination-associated deletion (B450 kb). 16 These conditions might enable the L1-mediated NAHR to cause disease, although the possibility of microhomology-mediated replication-dependent recombination models, such as fork stalling and template switching, microhomology-mediated break-induced replication and serial replication slippage, could not be ruled out. 17 The deletion size of exon 9 in the patients reported by Astuti et al 2 , found in two Dutch pedigrees and one cell line established from a Caucasian patient, strongly suggests the same mechanism at work, although this was not mentioned.…”
Section: Discussionmentioning
confidence: 99%